REINTEGRASI KINERJA TIM DALAM LENSA EPIDEMIOLOGI MANAJERIAL DAN DETERMINAN SOSIAL: TINJAUAN LITERATUR MODEL KOMUNIKASI ORGANISASI, KEPERCAYAAN, DAN KOMITMEN PADA RSUD PROVINSI NTB - Laily Indrayanti Yusuf; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: The effectiveness of healthcare services at RSUD Provinsi NTB heavily relies on team synergy, which is often fragmented by bureaucratic complexity and work pressure. Reintegrating team performance is crucial to ensuring patient safety and organizational sustainability. Objective: This study aims to analyze how organizational communication models, trust, and commitment influence the reintegration of team performance through the lens of managerial epidemiology and social determinants. Methods: This research employs a Systematic Literature Review (SLR) approach. Literature searches were conducted on Scopus and Google Scholar databases covering the period 2014–2024. Article selection followed the PRISMA protocol, resulting in a set of selected articles analyzed qualitatively. Results: Findings indicate that transparent organizational communication is a primary predictor of inter-professional trust. This trust acts as a mediator that strengthens staff's affective commitment. From a managerial epidemiology perspective, these factors are social determinants capable of reintegrating declining team performance. Conclusion: The success of RSUD Provinsi NTB in enhancing team performance depends on management's ability to manage organizational social determinants by strengthening the communication climate and a culture of mutual trust.